Tunable Single-Photon Generation in a Scanning Electron Microscope based on Silicon Photonics - Sirotin, Maxim; Chlouba, Tomas; Shiloh, Roy; Hommelhoff, Peter (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Single-photon sources play a pivotal role in quantum information technology and quantum sensing [1]. Quantum dots and color centers allow the creation of single photons on demand, are capable of generating higher Fock states and can be electrically driven [1,2]. Spontaneous parametric down-conversion and spontaneous four-wave mixing, in turn, serve as widely tunable sources of heralded single photons and complex quantum states [3]. The generation of photons radiated from swift free electrons makes it possible to obtain a broad spectrum, amplification, and electron-photon entanglement. Using flatband resonances and microcavities may even enhance the processes [4,5]. Modulation of free electrons enables the construction of photonic cat and GKP states, which are crucial for fault-tolerant quantum computing [6]. Recently, the effect of generating 1550 nm photons from free electrons directly into a nanophotonic Si3N4 ring resonator in a transmission electron microscope (TEM) at 120 keV has been experimentally shown [5].
Created from Fastlane, Scopus look-up